KUALITAS LAPORAN KEUANGAN DESA MELALUI APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI KECAMATAN WARUNGKIARA KABUPATEN SUKABUMI - Asep Hikmat (Mimbar Administrasi Mandiri, 2022)
The village financial report is an important financial position that comes from transactions carried out by the village government and is a medium for an entity to account for its activities to the public and also serves to provide information in making decisions and evaluating the performance of local governments. Therefore, the financial information presented must have value so that the financial information can be useful for its users. To increase accountability for the use of village fund budgets, each village is required to make an accountability report for the use of village finances. The use of the village financial information system (Siskeudes) in the preparation of village financial accountability reports is expected to improve the quality of the report. The results of the analysis of the quality of village reports in the Warungkiara District, Sukabumi Regency, concluded as follows: (1) The aspect of the relevance of the financial statements has been met quite well, (2) The reliability aspect of the financial statements has been met quite well, (3) The aspect of ability to be compared financial statements have been fulfilled quite well, and (4) the aspect of ease of understanding of Sukabumi's financial statements has been fulfilled quite well.